Effect of Local Admixture Ipomoea Asarifolia (Ajara) on the Strength Characteristics of Stabilized and Unstabilized Lateritic Blocks - L. A. O, Ogunjimi; F. S, Alabi; T. F, Adepoju; O. S, Agbonjinmi; U. D, Offiong; J. A, Osunade (Review of Energy Technologies and Policy Research, 2017)
This paper presents a summary of the results of a study on the use of a local admixture Ipomoea asarifolia (‘Ajara’) on the compressive strength and weight of specimens made from both cement stabilized and unstabilized lateritic soils. The effect of Ipomoea asarifolia extractions on the strength characteristic of lateritic blocks was investigated. Three mix proportions of cement: laterite of 0:1, 1:2 and 1:4 using lateritic soils from four different locations from around Ife while using six concentration levels of extracted liquid of Ipomoea asarifolia (0; 20; 40; 60; 80 and 100%) in fresh water as the mixing “water” (fluid). Ipomoea asarifolia specimen was analyzed to determine constituent chemical composition and their effect in reaction with other materials. Sieve analysis of the lateritic of the lateritic soil mix was carried out while a total of 132 – 100 mm cubes size were tested using a 1570 kN Avery-Denison Compression Testing Machine.